External condition to eco-behaviours in Melaka Green city - Bakar A.A.; Mustapa S.I.; Mohammad N. (Malaysian Institute Of Planners, 2023)
External Condition [EC] to eco-behaviours relates to the macro context of a person representing the persons faade towards his context. EC manifests in the perception and attitude towards surrounding circumstances such as the accessibility to conducive natural surroundings, encouragement to pro-environmental behaviours, convenience to be environmentally responsible and favourable law enforcement. Issue: 10 years has passed since the Green City Action Plan [MGCAP] and Sustainable Urban Development Framework [SUDF] were introduced. The Melaka EC to eco-behaviours needs to be assessed to determine the impact of the MGCAP and SUDF to EC of eco-behaviours. Purpose: This paper aims to compare the EC of Melaka residents to residents of other states in Malaysia. Approach: One-Way MANOVA was generated to determine the mean distribution of 10 EC items, across Malaysia States. Findings: There were significant differences within subjects of the 10 EC items between-subjects of Malaysia States. The Post-Hoc Test indicated almost all of the means of EC items for Melaka were higher than other states. The MGCAP and the SUDF shows a positive impact on the EC to a sustainable community. 2020 Malaysian Institute Of Planners. All rights reserved.